Customer satisfaction towards service delivery of the District Office of Papar / Annette Evangeline Ajin - Ajin, Annette Evangeline (2016)
The service delivery that provided by the Papar District Office give influence towards the customer satisfaction. The efficiency of service delivery at any local authorities or government agencies, will provide higher satisfaction towards the services that delivered to the customer. The study explores the customer satisfaction towards the Papar District Office. Moreover, the study also examines the service delivery that provided by the Paper District Office in terms of efficiency. A random sample of 100 respondents was targeted as the study's sample through the distribution of a questionnaire survey. The questionnaire survey were provided with two sections of questions which is open-ended questions, which is the respondent's personal background or also known as their demography; and close-ended questions, which is the respondent's personal view towards the services that delivered to them. The findings show that the most of the respondents satisfied with the quality of service that provided by the Papar District Office. In terms of the relationship between the elements of services that delivered by District Office and customer satisfaction shows that timeliness is the highest compared to other elements of services that delivered by the Papar District Office. However, the findings didn't represent the paper citizen as a whole due to the number of respondents are only based on 100 people only. Thus, the result of the study is only based on personal satisfaction with the service delivered by the Papar District Office.